A Study Investigating the Role of 2 Candidate SNPs in Bax and Bcl-2 Genes in Alzheimer’s Disease - Erdal, Mehmet Emin; Görücü Yilmaz, Senay; Ay, Mustafa Ertan; Güler Kara, Hale; Avci Özge, Aynur; Tasdelen, Bahar (Puerto Rico Health Sciences Journal, 2020)
Objective: The proto-oncogene Bax (Bcl-2-associated X protein) and related protein Bcl-2 (B-cell chronic lymphocytic leukemia/lymphoma-2) genes are triggers of apoptosis in Alzheimer’s disease (AD). The balance of these proteins has an important role in the death or life of a neuronal cell, and the functional polymorphisms in genes expressing these proteins have been found to promote apoptosis. To investigate the role of Bax and Bcl-2 genes in AD, we examined the presence of the 2 polymorphisms in peripheral blood. To our knowledge, this is the first clinical association study of these 2 functional SNPs using the peripheral blood of patients with AD. Methods: Bax (rs4645878) and Bcl-2 (rs2279115) in Alzheimer’s patients (N = 132) and healthy controls (N = 109), aged 65 to 85 years, were analyzed by qPCR (Quantitative Polymerase Chain Reaction) using TaqMan probe technology. Statistical analyses were done using SPSS, 11.5. The differences between groups were analyzed using an independent-samples t test. The relationships between genotypes and alleles were analyzed using chi-square or likelihood ratio test. The Hardy–Weinberg balance was checked for the patient and control groups. A p-value of less than 0.05 was taken as significant. Results: Sporadic AD patients and non-demented age matched control subjects were genotyped in this case-control study. No statistically significant relationship was found between the patients and controls for allele or genotype frequencies (p>0.05). Conclusion: Our data suggest that these two polymorphisms do not contribute to AD in the population from the Mersin region of the Eastern Mediterranean. Further studies with larger sample sizes must be conducted to ascertain the association between the 2 polymorphisms.